PENGARUH PENGGUNAAN MODEL PEMBELAJARAN TEAM QUIZ TERHADAP MOTIVASI BELAJAR PPKn SISWA SMK N 1 KOTA PEKANBARU - Ayola, Nursatry; Erlinda, Sri; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the low motivation of learning PPKn of the students at SMK N 1 Kota Pekanbaru. The formulation of the problem in this research is "Is there any significant effect of using Team Quiz learning model to students’ motivation in learning PPKn at SMK N 1 Kota Pekanbaru ?". This study aims to determine the effect of using Team Quiz learning model to students’ motivation in learning PPKn at SMK N 1 Kota Pekanbaru. This research was conducted at SMK N 1 Kota Pekanbaru in April 2018. This research was a quantitative descriptive which is experimental research which the students of grade X SMK N 1Kota Pekanbaru became the population in this study. The sample in this research was taken based on "Random Sampling" technique. Where the class taken into the sample was students of class X MB2 (experimental class) given the learning model of Team Quiz, and class X ADP1 (control class) were students who were given the conventional method. Then data analysis by using homogeneity test and "t" test. Based on the result of research indicated that there was an effect of learning motivation between student who using Team Quiz learning model and conventional method in SMK N 1 Kota Pekanbaru ( > ). Where there was an average increase to motivation in learning PPKn of experimental class from 19.17 to 26 and the average of PPKn learning motivation of control class from 19,16 to 19,63. Thus the hypothesis which reads that there is an effect of using Team Quiz learning model to students’ motivation in learning PPKn at SMK N 1 Kota Pekanbaru, can be accepted.Key Words: Team Quiz, Learning Motivation